Healthy Eating Policy for a provincial health authority in Atlantic Canada. (30th September 2020) - Kennedy, L; Nicholson, T; MacDonald, B; Jago, E; Mah, C
Abstract: Issue: Poor diets, the global leading cause of death and disability, are influenced by individual and community factors. Community health care settings have the potential to shape dietary behavior through food and beverage environments, and a healthy eating culture that supports the healthier choice as the easier choice. Description of the Problem: The Nova Scotia Health Authority (NSHA) is a provincial government health authority in Atlantic Canada, responsible for delivering services to nearly 1 million people in 10 hospitals, 8 ERs, and 135 community locations. The NSHA employs over 23, 400 health workers. In 2015, the NSHA centralized its governance, merging 9 regional health districts into one. Policies and procedures were re-written with a provincial focus, including a new Healthy Eating Policy (HEP) adopted in 2018. In this paper, we discuss the implementation of the HEP as a case study for how healthy eating can be fostered through continuous quality improvement. Results: The policy upholds NSHA as a community leader working collaboratively with internal and external partners. To be a credible leader in changing the landscape around healthy eating, NSHA agrees to "walk the talk" and model an evidence-based healthy eating policy. A hospital in Halifax piloted pricing, placement and promotion interventions to further support healthier eating. These have been expanded to other sites across NS. Lessons: 1) Internal Capacity Building - A Healthy Eating Steering Committee promotes healthy eating across the health system, including initiatives in partnership with auxiliaries, foundations and staff. 2) Improving Evaluation Infrastructure- The interventions led to strategic thinking of future point of sale systems and ways to improve data collection for evaluation 3) Academic Partnerships - NSHA and Dalhousie University formed a collaborative partnership to strengthen evaluation capacity making use of the latest evidence and methods from food environments research. Key messages: The Nova Scotia Health Authority's Health Eating Policy supports healthy eating across the province, and promotes supportive environments where the healthier choice is the easier choice. A hospital site in Halifax, NS, implemented a variety of pricing, placement and promotion interventions to promote a healthy workplace environment for employees and community members.